The Flexibility in Power System with High Photovoltaic Penetration into Extra-High Voltage Level - (:unkn) unknown (Springer, 2020)
The governments are adopting the use of renewable energy sources in electricity generation due to reasons such as the increasing climate change and energy supply security concerns and the rise of energy demand. Therefore, the share of variable renewable sources, especially solar energy, in total installed power capacity increases day by day. The power systems with the integration of solar energy sources transform. A power system to cope with high shares of variable solar generation needs to be flexible. In this chapter, the power system flexibility concept, the effect of variable renewable energy penetration, especially power plants on power systems flexibility, are examined. In addition, simulation studies are carried out for PV power systems penetration into extra-high voltage levels, necessary regulations for grid codes are determined, and solution methods are presented. © 2020, The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: High‐penetration photovoltaic; Photovoltaic power systems; Power grids; Power system stability; Power system stability